2020
DOI: 10.1101/2020.04.27.20082180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydroxychloroquine is associated with slower viral clearance in clinical COVID-19 patients with mild to moderate disease: A retrospective study

Abstract: Background: There is conflicting data regarding the use of hydroxychloroquine (HCQ) in COVID-19 hospitalized patients Objective: To assess the efficacy of HCQ in increasing SARS-CoV-2 viral clearance Design: Retrospective observational study Setting: Cleveland Clinic Abu Dhabi Participants: Hospitalized adult patients with confirmed SARS-CoV-2 infection Intervention: None Measurements: The primary outcome was the time from a confirmed positive nasopharyngeal swab to turn negative. A negative nasopharyngeal … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 20 publications
1
51
1
Order By: Relevance
“…Our meta-analysis did not reveal a clinical bene t of HCQ/CQ on in-hospital outcomes for patients with COVID- 19. The use of HCQ/CQ did not result in rapid viral clearance on RT-PCR.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Our meta-analysis did not reveal a clinical bene t of HCQ/CQ on in-hospital outcomes for patients with COVID- 19. The use of HCQ/CQ did not result in rapid viral clearance on RT-PCR.…”
Section: Discussioncontrasting
confidence: 51%
“…Later on, four other observational studies reported con icting results on viral clearance at different time-points during the disease. Mallat J et al [19] reported that viral negativity was signi cantly lower with HCQ compared to control group, whereas studies from Chen X et al [20] and Huang M et al [21] did not observe rapid viral clearance by CQ. A large multi-center cohort containing 373 patients (mainly mild to moderate COVID-19) by Huang MX et al [14] reported a signi cantly higher rate of viral clearance at Day 10 (91.0% vs 57.0%) and Day 14 (96.0% vs 80.0%) in the CQ treatment group.…”
Section: Discussionmentioning
confidence: 97%
“…The risk of bias among the included RCTs, assessed by the Cochrane risk of bias tool, is presented in Figures 2 and 3. Among the observational studies, one was considered to be at low risk, [19] eight at moderate risk, [20][21][22][23][24][25][26][27] seven at serious risk [12,[28][29][30][31][32][33] and one at a critical risk of bias [5].…”
Section: Characteristics Quality and Risk Of Bias Assessment Of Thementioning
confidence: 99%
“…The median time from con rmed positive to negative nasopharyngeal swab results were 17 days in the HCQ treatment group and 10 days in the control group (P=0.023). It is worth noting that HCQ was administrated at an early stage of the disease course in Mallat's study [29].…”
Section: Discussionmentioning
confidence: 99%